2007
DOI: 10.1889/1.2785461
|View full text |Cite
|
Sign up to set email alerts
|

14.2: A General Theory of Light Recycling with Light Pipes/Tunnels and Their Applications in LED Illuminators

Abstract: A general theory on light-pipe/tunnel-based recycling schemes, along with some experimental data obtained from LED illuminators, is presented in this paper. Light recycling is classified as angular, spatial, or mixed based on the angular filtering characteristics of the recycling process. The principles behind the three schemes are analyzed and some experimental results are presented at the end.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
1

Year Published

2008
2008
2011
2011

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 3 publications
0
1
1
Order By: Relevance
“…It can be shown that the brightness enhancement effect reported in figure 2 is not as pronounced as that reported for the light pipe based recycling systems in our previous publications 2, 3 . The main reason, we believe, is the strong dependence of the recycling efficiency of an angular recycling system such as the recycling collar on the surface scattering characteristics of the LED chip (the recycling light pipe is a spatial recycling system whose efficiency does not depend on LED surface roughness).…”
Section: Fig 2 Brightness Enhancement Vs Collection Cone Anglescontrasting
confidence: 43%
“…It can be shown that the brightness enhancement effect reported in figure 2 is not as pronounced as that reported for the light pipe based recycling systems in our previous publications 2, 3 . The main reason, we believe, is the strong dependence of the recycling efficiency of an angular recycling system such as the recycling collar on the surface scattering characteristics of the LED chip (the recycling light pipe is a spatial recycling system whose efficiency does not depend on LED surface roughness).…”
Section: Fig 2 Brightness Enhancement Vs Collection Cone Anglescontrasting
confidence: 43%
“…The etendue reduction ratio is the ratio of the total area of the output aperture over that of the uncoated window. The principle of enhancing brightness through light recycling has been explained in our previous work 5,6 . For the specific DPR system described above (output etendue = 50 mm 2 *steradian) and with a 4:1 etendue reduction ratio (recycling light pipe etendue = 200 mm 2 *steradian), simulation has shown that 40% of total lumen gain has been achieved.…”
Section: Fig 6 Output Aperture Of the Recycling Light Pipementioning
confidence: 99%